The effectiveness of using some criteria for determining adaptability on the example of winter rye cultivars - I. V. Safonova; N. I. Aniskov (Труды по прикладной ботанике, генетике и селекции)
Background. For most regions of Russia, winter rye is an indispensable grain and fodder cereal. Recently, winter rye crops have been declining. It is possible to improve this situation by releasing cultivars that ensure consistently high grain productivity under various growing conditions. Therefore, measuring the level of adaptability for yields in different mathematical quantities using a variety of methods is an urgent need.   Materials and methods. For an unprejudiced assessment of winter rye cultivars, the following adaptability parameters were calculated and analyzed: the intensity coefficient (I) and constancy of the stability index (Y) according to Udachin and Golovchenko; stability index (IS) according to Hangildin; range breadth (Jsp) according to Eberhart and Russell; breeding value (Sc) according to Hangildin; responsiveness coefficient (Cr.) according to Zykin; genotypic effect (Ɛi) according to Guryev; equalization coefficient (B) according to Dospekhov; multiplicativity coefficient (KM) according to Dragavtsev; and reaction effect (Er.) according to Novokhatin. Field experiments and the study of 8 winter rye cultivars were carried out according to VIR’s guidelines in 2012–2017.   Results and conclusion. A significant variation was found in grain yield; it was induced by the high contribution of the “year” factor (79.4 %). The best conditions for higher yields were formed in 2012 and 2015. An analysis of the six-year average yield showed that cvs. ‘Rushnik 2’, ‘Bereginya’, and ‘Novaya Era’ exceeded ‘Ilmen’ by 5–22 %. It was shown that among the selected ten indicators, worth attention were the multiplicativity coefficient, the stability index, the breeding value index, the reaction effect of a cultivars, and the range breadth index: they established the adaptability level of a cultivar with higher statistical significance. Cvs. ‘Novaya Era’, ‘Yanrarnaya, ‘Bereginya’, and ‘Vavilovskaya’ from the analyzed set demonstrated high adaptability.